Pengaruh Senam Kaki Diabetik Terhadap Nilai Angkle Branchial Index Pada Pasien Diabetes Melitus Di Persadia Cabang Kota Surakarta - Zaqiyah, Nur Rochma Laili, Fahrun Nur R, S.Kep., Ns., M.Kep (2017)
One of the complications of Type 2 Diabetes Mellitus affecting the peripheral nervous system that Arthery Peripheral Disease (PAD) is a condition where there are lesions in blood vessels, causing blood flow in the arteries that supply blood to the extremities is limited. Diabetic foot gymnastics can help blood circulation and strengthen the small muscles of the feet and prevent foot deformity, overcomes the limitations of the amount of insulin in patients with diabetes lead to increased blood sugar levels it causes damage to blood vessels, nerves and structures. The blood circulation in the foot area can be measured through a non-invasive examination of one of them is the examination of the ankle brachial index. This study aims to examine Effect Against Diabetic Foot Gymnastics angkle Value Brachial Index in Patients Diabetes mellitus in Persadia branch of Surakarta. This study is a quasi experimental studies with pre-test and post-test. The study population was patients with diabetes mellitus who actively participates in the activities of the branch Persadia Surakarta, the study sample as many as 44 people with purposive sampling technique. Collecting data using a sphygmomanometer and stethoscope study and were analyzed by paired sample t-test and Wilcoxon Signed Rank Test. This study concluded that there were significant differences in pre-test and post-test value angkle Brachial Index (ABI) following a diabetic foot exercise in patients with type 2 diabetes in Persadia Branch of Surakarta,